Efforts to Increase the Independence of NU Ranting Wates Through Institutional Cooperation Among NU Branches in Tanjunganom Subdistrict - Saini, Mukhamat; Mufidah, Luluk Indarinul; Sujoko , Sujoko; Khoiriyah , Anatul; S, Nadia Amalinatus; Asmoro , Nur (STAI Miftahul ULa Nganjuk, 2023)
This community service project aimed to address critical socio-economic challenges faced by a rural community through educational empowerment, local entrepreneurship, and leadership development. Using Participatory Action Research (PAR) methodology, the project involved active collaboration between researchers and community members in all stages, from identifying issues to implementing solutions. Educational programs focused on enhancing literacy, vocational skills, and digital competencies, while entrepreneurial workshops aimed to promote local business development. The project also fostered local leadership, encouraging community members to take active roles in decision-making processes. Results showed significant improvements in skill acquisition, business creation, and leadership capacity, although challenges related to resource limitations and gender inclusivity were identified. This research demonstrates that community-driven initiatives, when properly supported, can lead to sustainable social and economic transformations